Towards Sustainable Afforestation: Greening an Indian Metropolis - Sen, Supatra (Indian Forester, 2023)
Due to population, pollution and industrialization, cities are in the forefront of socio-economic and health crises. Sustainable cities must now target resilience by the recovery of urban greens, protecting nature and natural resources from rapid urbanization, creating green jobs and means to livelihood. Crucial ecosystem services are provided by urban green spaces viz. community parks and gardens, green roofs, urban forests, natural water-bodies and such others. ’Right place, right tree’ is the key to intelligent urban greening. Every effort and thought must be spared to careful selection of appropriate plant material based on habit, colour, season of flowering, form, rate of growth and environmental conditions. Pro-environmental planning, nature-based solutions and sustainable outlook could go a long way in positively affecting the city’s biodiversity index, green urbanization as well as mental health and well-being of urban dwellers.